Delinquency Hostile to Women – a Hurdle for Sustainable Development in Multidimensional Outlook - Gayathri, N.; Karthikeyan, P. (Problemy Ekorozwoju, 2015)
Violence against women is partly a result of gender relations that assumes men to be superior to women. Given the subordinate status of women, much of gender violence is considered normal and enjoys social sanction. Violence against women has been clearly defined as a form of discrimination in numerous documents. Cultural and social factors are interlinked with the development and propagation of violent behaviour. With different processes of socialization that men and women undergo, men take up stereotyped gender roles of domination and control, whereas women take up that of submission, dependence and respect for authority. A female child grows up with a constant sense of being weak and in need of protection, whether physical social or economic. This helplessness has led to her exploitation at almost every stage of life which remains a hurdle for the sustainable development of the nation. With almost half the population feeling insecure can a nation really progress towards development? Can women be called safe in any part of the world? Be it within the boundaries of the State or beyond? Cross-border crimes not just affect the women of the particular Nations at war but it travels beyond the borders and becomes an issue of global concern. This paper discusses the crime against women comparing and relating it with various aspects of sustainable development like literacy rate, political participation of women, unemployment and sex ratio with solutions to bring a change and development towards a better tomorrow.